Negotiating brotherhood: Habitus, capital and the transformation of Orang Basudara - Steve Gerardo Christoffel Gaspersz (Center for Sociological Studies and Community Developmen, 2026)
This qualitative study explores the concept and praxis of Orang Basudara (Brotherhood) in Malukan culture by employing Pierre Bourdieu’s theory of practice as the main analytical framework. It examines how habitus, symbolic capital, and symbolic power shape, reproduce, and transform the social solidarity embedded in Orang Basudara amid processes of modernization and globalization. Through a qualitative socio-historical approach, data were analyzed to understand how social structures and cultural dispositions interact within everyday practices in Maluku. The findings reveal that Orang Basudara is a dynamic product of the dialectical relationship between historical structures and human agency. This study identifies tensions between traditional communal values and contemporary individualistic tendencies influenced by global capitalism. The uniqueness of this article lies in developing a new Bourdieusian-relational framework that integrates habitus transformation with the concept of cultural negotiation, offering an innovative lens to explain how local solidarity practices adapt to social change. Hence, Orang Basudara is not a static moral ideal but an evolving field of social interaction that continuously negotiates between local wisdom and modern social forces.